The relation of leadership mindset capacity and worker cohesion to the organization influences the business efficiency of small and medium-sized enterprises (SME) In Ho Chi Minh City - Hung, MBA Bui Quang; Tuan, Nguyen Minh (Edelweiss Applied Science and Technology, 2024)
This study aims to help administrators perceive a specific perspective on the importance of cognitive capacity, from which they can take measures and make changes in work, study, training, and the managing process to improve workers’ cohesion in the organization and business efficiency. Research methods using a pre-made questionnaire, a survey is used to gather data for official quantitative research. According to Hair et al. (2006); Kline (2011); Tabachnik and Fidell (2011), factor analysis and linear structure were performed using Structural Equation Modeling (SEM) using the SmartPLS tool. This is because the theoretical model has interwoven relationships, so the linear structural model (Structural Equation Model, SEM) is used to test the above hypotheses (Lorence and Mortimer, 1985; Anderson and Gerbing, 1988). In the study, there are 3 variables that receive impact from other variables: HQ, NLLD, and SGK. The adjusted R-squared of Effectiveness (HQ) is 0.328, so the independent variables affecting it include Leadership Mindset Capacity (NLLD) and Cohesion (SGK) explains 32.8% variation (variance) of the HQ variable. The adjusted R-squared of Leadership Mindset Capacity (NLLD) is 0.784, so the independent variable affecting it explains 78.4% of the variation (variance) of the NLLD variable. Scientifically speaking, this study enriches the research on business efficiency, leadership mindset capacity, worker cohesion in the organization, and forming the thinking capacity scale in addition to business efficiency scale. Furthermore, this study can be used as a reference for other authors to suggest new research issues. Practical Implications, the Thinking Capacity scale, which was established from the research results, can be used to evaluate the administrators’ proficiency in many different goals such as learning, personnel recruiting, training, and improving personnel’s abilities.